2013
DOI: 10.1007/s10459-013-9448-6
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-event analysis of individual variables associated with nursing students’ academic failure: a longitudinal study

Abstract: Empirical studies and conceptual frameworks presented in the extant literature offer a static imagining of academic failure. Time-to-event analysis, which captures the dynamism of individual factors, as when they determine the failure to properly tailor timely strategies, impose longitudinal studies which are still lacking within the field. The aims of this longitudinal study were to investigate the time which elapses from a nursing student's admission to a Bachelor of Nursing program to their academic failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…A group of nursing students pursuing their bachelors level nursing degree in Italy were involved. Their demographic profile was in line with that previously documented in other studies performed in the Italian context [ 34 , 35 ], and their size was appropriate with respect to the number of items included in each instrument. The ratio of one-item/10 participants was considered congruent with the target sample size established beforehand according to the recommendations stated by Pett and colleagues [ 36 ].…”
Section: Discussionsupporting
confidence: 77%
“…A group of nursing students pursuing their bachelors level nursing degree in Italy were involved. Their demographic profile was in line with that previously documented in other studies performed in the Italian context [ 34 , 35 ], and their size was appropriate with respect to the number of items included in each instrument. The ratio of one-item/10 participants was considered congruent with the target sample size established beforehand according to the recommendations stated by Pett and colleagues [ 36 ].…”
Section: Discussionsupporting
confidence: 77%
“…This project included only the experiences of full-time undergraduates, but, of course, commuting students can be full-and part-time postgraduates, too. Dante, Fabris and Palese (2013) found that living over thirty minutes from campus directly correlated with medical students' likelihood of academic failure. State University (2013), cited in Helsen (2013), suggests that commuter students felt, because of their travel commitments, that they lacked the extra time to devote to finding resources or to talk to teaching staff.…”
Section: Background Literaturementioning
confidence: 97%
“…A pre-post intervention non-equivalent control group design evaluating the effects of a complex intervention composed of several components interacting with each other (Anderson, 2008) was conducted in two Bachelor of Nursing Degree admitting students with a demographic profile similar to that documented in previous Italian nursing education studies (Dante et al, 2013). The complex intervention applied to the treatment and control group was based upon the literature available and upon on the standards assured in the Bachelor's during the last three years: therefore, any change was procured by the research project, characterising this pre-post intervention study design as pragmatic in nature (Craig et al, 2012), capturing the differences in the real word.…”
Section: Participantsmentioning
confidence: 99%